Computational fluid dynamics simulations of spray tests in a multicompartment construction with an Eulerian–Lagrangian approach - Lu, Yazhe; Ran, Xu; Wei, Zonglan (Frontiers in Energy Research, 2024)
This paper is an investigation of the gas mixing and depressurization effects of containment spray on hydrogen risk during a typical severe accident in a light water reactor (LWR). Two spray tests (ST3_0 and ST3_1) were simulated using the OECD/SETH-2 project frame; the tests were performed with different preconditions in two interconnected vessels of the PANDA facility by focusing on the breaking-up of the stratified helium-rich layer and helium transport between the interconnected vessels with and without heat and mass transfer. The computational fluid dynamics simulations were performed using an Eulerian–Lagrangian approach, in which the dispersed droplets were tracked with a Lagrangian framework and the heat and mass transfer model between the droplets and gas were developed through user-defined functions. The simulation results are in reasonable agreement with the test data and reproduce the main phenomena of the spray tests. Although the proposed approach is adequate for addressing similar problems, some discrepancies still exist in the simulations. Based on these discrepancies, some recommendations are suggested to improve the accuracy of the proposed approach.